2019
DOI: 10.7150/thno.38425
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances and challenges of repurposing nanoparticle-based drug delivery systems to enhance cancer immunotherapy

Abstract: Cancer immunotherapy is an attractive treatment option under clinical settings. However, the major challenges of immunotherapy include limited patient response, limited tumor specificity, immune-related adverse events, and immunosuppressive tumor microenvironment. Therefore, nanoparticle (NP)-based drug delivery has been used to not only increase the efficacy of immunotherapeutic agents, but it also significantly reduces the toxicity. In particular, NP-based drug delivery systems alter the pharmacokinetic (PK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 134 publications
(142 reference statements)
0
62
0
Order By: Relevance
“…The cumulative concentration of drugs can be increased in targeted tissues by means of the application of liposomes since they alter the biological distribution of the drugs. This phenomenon can be very useful because the other normal organs would not be affected by the deleterious impacts of anticancer drugs that can lead to the lower harmful effects . In the present study, we entrapped cisplatin in PEGylated nanoliposomes, and then, the characteristics and cytotoxicity of them were studied.…”
Section: Introductionmentioning
confidence: 96%
“…The cumulative concentration of drugs can be increased in targeted tissues by means of the application of liposomes since they alter the biological distribution of the drugs. This phenomenon can be very useful because the other normal organs would not be affected by the deleterious impacts of anticancer drugs that can lead to the lower harmful effects . In the present study, we entrapped cisplatin in PEGylated nanoliposomes, and then, the characteristics and cytotoxicity of them were studied.…”
Section: Introductionmentioning
confidence: 96%
“…The 2018 Nobel Prize in physiology or medicine was awarded to pioneers in the field of cancer immunotherapy, which has been a tremendously successful area of work [45]. Tumor immunotherapy has been widely explored in various fields, such as nanotechnology-enhanced immunotherapy [46,47].…”
mentioning
confidence: 99%
“…Investigation into the mechanisms behind the trigger for this anti-tumor immunity remains an interesting pursuit. Notably, recent studies have found that certain chemotherapies 38 , PTT 39 , photodynamic therapy 40 - 42 and other treatments 43 - 45 can initiate an antitumor immune response by inducing tumor cells to undergo immunogenic cell death (ICD). Furthermore, cancer cells undergoing ICD can release immunostimulatory damage-associated molecular patterns (DAMPs) that act as potent danger signals, including calreticulin (CRT) exposure on the surface of tumor cells, release of large amounts of high-mobility group box 1 (HMGB1) or extracellular secretion of adenosine triphosphate (ATP).…”
Section: Resultsmentioning
confidence: 99%